Intonation analysis in news reading by Palki Sharma: A suprasegmental approach - Hanidia, Nauvalia; Bowo, Tri Are; Lubis, Donal Fernado (Jurnal CULTURE (Culture, Language, and Literature Review), 2025)
This study analyzes the use of intonation in news reading by Palki Sharma with a suprasegmental approach in the news Ukraine War: Understanding Russian President Vladimir Putin. This study aims to identify the types and functions of intonation used by Palki Sharma based on the suprasegmental theory proposed by Collins & Mees (2013).  The data in this study were collected from recordings of news broadcasts hosted by Palki Sharma and analyzed using a PRAAT voice analyzer, which functions to analyze sound. This research uses a qualitative descriptive method, where the data collected is transcribed, categorized, and analyzed to determine the type of intonation, the function of the intonation used, and the attitude shown by Palki Sharma through the intonation she produces. The results show that out of 66 data containing Palki Sharma's attitudes and emotions, she predominantly uses low fall intonation (33 data) to show assertiveness and concern, rise-fall intonation (26 data) to convey sarcasm and skepticism, fall-rise intonation (5 data) appears in the context of correction or reminder of a fact, high rise (1 data) which shows curiosity, and high fall (1 data) is used in the context of dramatizing Functionally, Sharma's intonation highlights important points, expresses attitude, clarifies sentence structure, and builds a serious news atmosphere. This study also shows that Palki Sharma's intonation not only conveys information but also forms a critical opinion towards Putin.